Penerapan Metode Fuzzy Tsukomoto untuk Mengukur Tingkat Kelayakan Produk - Desyanti Desyanti; Denok Wulandari; Dewi Anjani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Micro, Small and Medium Enterprises are one of the business fields that are in great demand by the public. MSMEs have their own advantages, namely that they can more easily carry out product development and can survive during an economic crisis. However, product feasibility is something that must be considered in MSME activities because it can provide benefits in terms of financial and social benefits. With a feasibility analysis, it is hoped that the risk of failure in marketing the product can be avoided. One of the MSMEs in the city of Dumai is X Cookies, a business that was built in 2019 and has many consumers who come to buy products from this home business, both in small and large quantities. To improve the quality of product suitability, you must evaluate the quality of the product provided to consumers whether it meets the expectations and desires of consumers or not. By using Tsukomoto's fuzzy logic, the level of suitability of X Cookies products can be determined. From the research carried out, the product feasibility level was not feasible = 0.39155 and feasible = 0.60845. So it can be said that the feasibility level for the X Cookies brownie product is at a feasible level.